2014
DOI: 10.1292/jvms.14-0028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Bacteria-Based Probiotic on Ruminal pH, Volatile Fatty Acids and Bacterial Flora of Holstein Calves

Abstract: Twelve ruminally cannulated Holstein calves (age, 12 ± 3 weeks) were used to identify the effect of a probiotic comprised of Lactobacillus plantarum, Enterococcus faecium and Clostridium butyricum on ruminal components. The calves were adapted to a diet containing a 50% high-concentrate (standard diet) for 1 week, and then, the probiotic was given once daily for 5 days (day 1–5) at 1.5 or 3.0 g/100 kg body weight to groups of four calves each. Four additional calves fed the standard diet without probiotic serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
40
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 38 publications
8
40
3
1
Order By: Relevance
“…Numerous studies have reported beneficial effects of probiotics on the health status and performance of calves (Mudgal and Baghel 2010;Bayatkouhsar et al 2013;Qadis et al 2014;Soto et al 2014). Most of the experiments showed increased weight doi: 10.17221/8727-CJAS gain and improved feed conversion ratios, but few studies also monitored a long-term survival of the probiotics administered.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported beneficial effects of probiotics on the health status and performance of calves (Mudgal and Baghel 2010;Bayatkouhsar et al 2013;Qadis et al 2014;Soto et al 2014). Most of the experiments showed increased weight doi: 10.17221/8727-CJAS gain and improved feed conversion ratios, but few studies also monitored a long-term survival of the probiotics administered.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strongly acidic and proteolytic conditions in animal stomachs [Bilik et al, 2014;Dono et al, 2014;Moesseler et al, 2010Moesseler et al, , 2012Mohammed et al, 2014;Olukosi and Dono 2014;Qadis et al, 2014], the stability and activity of phytase under gastric conditions can be critical to its catalytic efficacy. However, only several phytases reported to date were characterized as stable under gastric or acidic conditions Fugthong et al, 2010;Garrett et al, 2004;Huang et al, 2008;Singh and Satyanarayana, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…plantarum , E . faecium and Clostridium butyricum on the ruminal components of weaned calves [20]. In this study, we examined the effects of different doses of a multi-strain BP on ruminal pH and VFA, lactic acid, ammonia nitrogen (NH 3 -N) and plasma metabolite concentrations in cattle with SARA.…”
mentioning
confidence: 99%